Parents of Children With Cancer: At-Risk or Resilient? - Phipps, Sean (J Pediatr Psychol, 2015)
Objective To examine adjustment in parents of children with cancer using a design that minimizes focusing effects and allows for direct comparison with parents of healthy children. Method Parents of 305 children with cancer and a demographically similar sample of 231 parents of healthy children were evaluated using diagnostic interviews for posttraumatic stress disorder (PTSD), and questionnaire measures of posttraumatic stress symptoms (PTSS) and psychological growth (PG), as well as measures of global psychological functioning. Results Rates of current and lifetime PTSD in parents of children with cancer were low, and did not differ from comparison parents. Likewise, levels of PTSS were not significantly different from comparison parents, but differed as a function of time since diagnosis, with parents of children who were ≥5 years from diagnosis reporting significantly lower PTSS than comparison parents. PG was higher in parents of children with cancer than in comparison parents regardless of time since diagnosis. Conclusion Parents of children with cancer demonstrate resilience to this challenge.